Implementing Practice Guidelines: A Workshop on Guidelines Dissemination and Implementation with a Focus on Asthma and COPD - Louis-Philippe Boulet; Allan Becker; Dennis Bowie; Paul Hernandez; Andrew McIvor; Michel Rouleau; Jean Bourbeau; Ian D Graham; Jo Logan; France Légaré; Thomas F Ward; Robert L Cowie; et al. (Canadian Respiratory Journal)
The present supplement summarizes the proceedings of the symposium “Implementing practice guidelines: A workshop on guidelines dissemination and implementation with a focus on asthma and COPD”, which took place in Quebec City, Quebec, from April 14 to 16, 2005. This international symposium was a joint initiative of the Laval University Office of Continuing Medical Education (Bureau de la Formation Médicale Continue), the Canadian Thoracic Society and the Canadian Network for Asthma Care, and was supported by many other organizations and by industrial partners. The objectives of this meeting were to examine the optimal implementation of practice guidelines, review current initiatives for the implementation of asthma and chronic obstructive pulmonary disease (COPD) guidelines in Canada and in the rest of the world, and develop an optimal strategy for future guideline implementation. An impressive group of scientists, physicians and other health care providers, as well as policy makers and representatives of patients’ associations, the pharmaceutical industry, research and health networks, and communications specialists, conveyed their perspectives on how to achieve these goals.